Gender and Development - Kaistha,Sunitha; Sahaya,Amitta ed (Empowering women worldwide series :12, 2011)
This book is our endeavour to chart the emerging trends in the issues of women, work and health against the dynamics of today's globalized world. These changes touch the various spheres of women's lives related to the fields of: Gender & Development Gender, Work Health Sustainability Development in South Asia This book reflects the innovative thought processes of women across the world and the courage and determination manifested by them as they address the challenges that have come their way.